Perspectives of the COVID-19 pandemic and vaccination among racially and ethnically diverse gay, bisexual, and other men who have sex with men with and without HIV in the US South: findings from qualitative individual in-depth interviews - Jake S. Waldman; Jorge Alonzo; Lilli Mann-Jackson; Sandy K. Aguilar-Palma; Manuel Garcia; Benjamin D. Smart; Scott D. Rhodes (BMC Infectious Diseases)
Abstract Background The impact of COVID-19 on specific populations, including gay, bisexual, and other men who have sex with men (GBMSM), varies based on a range of factors such as access to health care, underlying health behaviors and conditions, and social determinants of health. Our community-based participatory research partnership sought to better understand perspectives about and experiences with the COVID-19 pandemic, COVID-19 vaccination, and related health care among GBMSM. Methods We collected, analyzed, and interpreted qualitative in-depth interview data from a diverse sample of GBMSM (N = 30) in North Carolina, USA. Using purposive sampling, we recruited native English (n = 15) and Spanish (n = 15) speakers and persons with HIV (n = 13) and persons without HIV (n = 17). We analyzed interview data using constant comparison, an approach to grounded theory. Results Participant mean was 33.4 (SD = 8.5) years. Sixteen themes emerged that were categorized into five domains: trust/mistrust of politicians, healthcare professionals, and the US government (n = 4 themes); engagement in COVID-19 prevention strategies (n = 2 themes); attitudes towards COVID-19 vaccination (n = 3 themes); access to and use of health care (n = 4 themes); and impact of COVID-19 on social determinants of health and mental health (n = 3 themes). Conclusions This research increases our understanding of the COVID-19 pandemic among particularly minoritized and underserved communities: racially and ethnically diverse, English- and Spanish-speaking GBMSM with and without HIV in the US South. By addressing the unique needs and concerns of these communities, we can promote more equitable public health responses; enhance preventive healthcare delivery; improve preparedness for subsequent outbreaks (e.g., mpox), epidemics, and pandemics; and be better equipped to support delivery and uptake of potential future preventive HIV vaccines among communities impacted by health disparities.